The productivity and competitiveness of the children’s apparel industry in Bucaramanga, in the dynamics of strategic management (2011)
This document is a summary of an investigation initiated by a study made in 52 companies of children’s clothing industry in Bucaramanga, in the year 2010. The study observed many variables relating to administrative actions, method of production, cost structure and functions of productive and competitive factors. The information obtained permitted the identification of the dynamics of these organizations and at the same time defined the bases for the establishment of strategic options oriented to the betterment of productivity and competition. These are related to the types of production, systems cost, technological platforms and administrative structure.